IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH THE INTERACTIVE COMPENSATORY MODEL - Nurul Izzah; Siti Azisah; Sitti Nurpahmi (Universitas islam Negeri Alauddin Makassar, 2021)
This research aimed at improving the students' reading comprehension of the first grade at Wahdah Islamiyah Makassar junior high school, which contains 25 students used a learning model called the interactive compensatory model. This research used Classroom Action Research (CAR) with two cycles. Each cycle consists of steps to planning, acting, observing, and reflecting. The data had collected by the form of quantitative and qualitative data. Quantitative data obtained by analyzing the observation checklist result, while quantitative data obtained through score processing used a particular formula. This research’s findings proved that applied the instructional model called the interactive compensatory model successfully improved students' learning abilities, especially in reading comprehension. The test results in the first cycle, was 1,660 or 66,4% and increased to 2,120 or 84,8%. In the first cycle, 14 students (56%) out of 25 students got the point under the minimum standard score (KKM), while those who reached the minimum standard (KKM) score were only 44%. However, after being given treatment in the second cycle, it was seen that 100% of the students exceed the minimum standard (KKM) score. The observation checklist results showed that students’ participation in the first Cycle increased in the second cycle. They became more active and dared to expressed their opinion.